Hidden skewness - Ludwig Ensthaler; Olga Nottmeyer; Georg Weizsäcker (Institute for the Study of Labor (IZA), 2010)
We provide laboratory evidence that people neglect skewness resulting from compound shocks.
urn:nbn:de:101:1-201009302460
Keywords: C91; D03; 330; skewness; belief biases; binomial tree